THE POSITION OF HYOID BONE IN DIFFERENT FACIAL PATTERNS: A LATERAL CEPHALOMETRIC STUDY - Amayeri, Mohammed; Saleh, Fayez; Saleh, Magda (European Scientific Journal, ESJ, 2014)
Considerable attention has been given to the position of the hyoid bone in relation to the facial skeleton. Studies on various population samples have shown that changes in the hyoid bone position seem to be related to changes in the mandibular position in particular and other facial structures in general. The present study was undertaken to evaluate the changes in the position of the hyoid bone which might induce changes in the position of certain dentofacial structures and it could be instrumental in the establishment of specific structural elements of the jaws and occlusion of teeth which is of great interest to the orthodontists. Lateral cephalometric measurements successfully assessed the relationship between different skeletal patterns and the hyoid bone and allowed to correlate the hyoid bone position to other craniofacial parameters. Statistically significant differences existed among the three groups in measurements of SNB, ANB and NSH. Statistically significant differences among Classes I, II and III as regards HSN perp, H-FH perp, H –C3, H- RGn and C3-Rgn.